Immunotherapy for head and neck cancer: advances and deficiencies - De Costa, Anna-Maria A. (2011)
The concept of immunotherapy as a treatment for cancer patients has been in existence for decades. However, more recent immune therapeutic approaches have involved targeting of tumor-specific antigens. While improvements have been made in using such immune stimulatory treatment strategies for a variety of solid cancers, the use of these strategies for patients with head and neck squamous cell carcinoma (HNSCC) is lagging behind. Immunotherapeutic approaches for HNSCC are particularly complicated by the profound immune suppression that is induced by HNSCC, which potentially lessens the effectiveness of immune stimulatory efforts. Trials involving patients with various solid cancers have shown the enhanced effectiveness of combining various immunotherapeutic approaches or combining immunotherapy with chemotherapy or radiation therapy. Treatment of HNSCC with such combination approaches has not been extensively investigated and has the added challenge of the need to overcome the HNSCC-induced immune suppression. This review focuses on clinical trials that have tested immunotherapeutic approaches for HNSCC patients and the challenges associated with such approaches. In addition, it will call attention to immunotherapeutic strategies that have been demonstrated as successful in the treatment of other solid cancers in order to identify potential strategies that may apply to the treatment of HNSCC.